Sagot :
ANSWERS:
A. Square of a Binomial
(7x - 2)² =
- [tex]\large{\boxed{\boxed{\sf\blue{49x² \: - \: 28x \: + \: 4}}}}[/tex]
(3x + 2y)² =
- [tex]\large{\boxed{\boxed{\sf\blue{9x² \: + \: 12xy \: + \: 4y²}}}}[/tex]
(x - 4y)² =
- [tex]\large{\boxed{\boxed{\sf\blue{x² \: - \: 8xy \: + \: 16y²}}}}[/tex]
(2x - 5)² =
- [tex]\large{\boxed{\boxed{\sf\blue{4x² \: - \: 20x \: + \: 25}}}}[/tex]
(5x + 8)² =
- [tex]\large{\boxed{\boxed{\sf\blue{25x² \: + \: 80x \: + \: 64}}}}[/tex]
B. Cube of a Binomial
(2x - 1)³ =
- [tex]\large{\boxed{\boxed{\sf\blue{8x³ \: - \: 12x² \: + \: 6x \: + \: 1}}}}[/tex]
(3x + y)³ =
- [tex]\large{\boxed{\boxed{\sf\blue{27x³ \: + \: 27x²y \: + \: 9xy² \: + \: y³}}}}[/tex]
(4x - 3y)³ =
- [tex]\large{\boxed{\boxed{\sf\blue{64x³ \: - \: 144x²y \: + \: 108xy² \: - \: 27y³}}}}[/tex]
(3y + 2)³ =
- [tex]\large{\boxed{\boxed{\sf\blue{27y³ \: + \: 54y² \: + \: 36y \: + \: 8}}}}[/tex]
(7x - 5y)³ =
- [tex]\large{\boxed{\boxed{\sf\blue{343x³ \: - \: 735x²y \: + \: 525xy² \: - \: 125y³}}}}[/tex]
#CarryOnLearning